The Role of Cultural Education in Shaping the Socialisation of Undergraduate Social Studies Students at the University Of Jos - Shittu Lukman Olayinka; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
This study investigated role of cultural education in shaping the socialisation of undergraduate social studies students at the University of Jos. The study was guided by three objectives and three corresponding research questions were answered. The study tested two null hypotheses. The study used a survey research design specifically cross-sectional survey research design. The study population comprised 416 undergraduate Social Studies students across 100 to 400 levels, excluding those who took Social Studies as an elective. A total of 200 students were selected as the sample, ensuring gender balance and equal representation from each academic level using simple random sampling technique. A structured questionnaire was used for data collection and was subjected to face and content validity by experts. The reliability was established at 0.82. The data collected were analysed using descriptive and inferential statics of mean and standard deviation for answering research questions and t-test was used in testing the hypotheses all through SPSS. The analysis revealed among other things that that, cultural education improves students' socialisation and sense of belonging and students have positive views about adding cultural education to their curriculum. The study concluded that cultural education is essential and key to socialization of students in all societies. The study also recommended among other things that, Universities should organise cultural awareness programmes and workshops to further promote students’ appreciation of cultural diversity and its role in fostering social cohesion and lecturers should adopt interactive teaching methods, such as storytelling, role-playing, and case studies, to make cultural education more engaging and relevant to students’ lived experiences.